PKM Pemberdayaan Kelompok Pengrajin Keripik Kalakai Sebagai Olahan Sayuran Lokal Berbasis Potensi Unggulan Daerah Lahan Basah - Noor Rahmini; rizali rizali; Muhammad Fathi; Widhya Rahmadhyani (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2023)
The Covid-19 pandemic paralyzed all walks of life including the Jaya Rezeki Family Income Improvement Business (UPPKS) business group. In facing the new normal, a special strategy is needed in developing the UPPKS so that it survives. One of them is through innovation in flavor variants, new processed variations, making product packaging attractive and creating less contact so that the UPPKS economy can survive and grow. UPPKS Jaya Rezeki, which is located in Antar Jaya Village in Marabahan District, Barito Kuala Regency, South Kalimantan Province, is one of those affected by the Covid-19 pandemic. Some of the problems found at UPPKS Jaya Rezeki consist of aspects of the variant flavor of kalakai chips, there is only one flavor variant, namely the original flavor of kalakai chips, aspects of processed kalakai variations where there is only one processed product of kalakai which has economic value, namely kalakai chips and there are no new innovations in variations. processed kalakai, aspects of product packaging that are able to maintain the quality of processed kalakai products and are attractive, and aspects of marketing technology where marketing and sales of UPPKS Jaya Rezeki are still done manually. The service team provides solutions to the problems faced, several solutions are offered, namely: 1) adding variants of the flavor of kalakai chips, including lime leaf kalakai chips, spicy kalakai chips, anchovies kalakai chips, and rebon prawn kalakai chips, 2) making product packaging which maintains the durability of product quality, is practical and attracts buyers, 3) makers of online payment systems to create less contact payments. Keywords: PKM, Kalakai chips, local vegetables, wetlands, Antar Jaya Village